Radiofrequency ablation combined with immunotherapy to treat hepatocellular carcinoma: a comprehensive review - Gui-Lin Xie; Zhi-Han Zhong; Tai-Wei Ye; Zun-Qiang Xiao (BMC Surgery)
Abstract Background and aim Hepatocellular carcinoma (HCC) is a highly immunogenic tumor and the third leading cause of cancer-related deaths worldwide with an increasing incidence. Therefore, the combination of immunotherapy with other approaches, such as anti-angiogenic agents and local area therapy, has become a new strategy for HCC treatment. Methods We searched PubMed and Web of Science and extracted publications relating to the radiofrequency ablation (RFA) and immunotherapy. The search terms were: “radiofrequency ablation”, “immunotherapy” and “hepatocellular carcinoma”, and manual searches of eligible articles from literature reference lists were performed. We then thoroughly reviewed the literature on ablation combined with immunotherapy for HCC, analyzed the relevant mechanism, and explored the safety and effectiveness of this form of combination therapy. Results RFA combined with immunotherapy in HCC is reported to have good efficacy and controllable safety. On the one hand, RFA can induce the immunogenic substances including Ficolin-3, IL-1 and heat shock protein and regulate the immune cells by mediating the Th1/Th2 ratio, increasing Th17 cells, etc. On the other hand, RFA treatment can lead to tumor immune microenvironment reconstruction, increasing the proportion of functional T cells and upregulate PD-1 in T cells in distant tumors without RFA. This combined strategy has the ability to enhance the anti-tumor immune response through synergies, significantly reduce the risk of recurrence and improve survival. Conclusions RFA combined with immunotherapy yields a good synergistic effect: it can further strengthen anti-tumor response, delay distant tumor growth, reduce tumor recurrence and metastasis, providing new options for HCC systemic treatment.